Decreased Fibrogenesis After Treatment with Pirfenidone in a Newly Developed Mouse Model of Intestinal Fibrosis. Issue 3 (5th February 2016) - Meier, Remo; Lutz, Christian; Cosín-Roger, Jesus; Fagagnini, Stefania; Bollmann, Gabi; Hünerwadel, Anouk; Mamie, Celine; Lang, Silvia; Tchouboukov, Alexander; Weber, Franz E.; Weber, Achim; Rogler, Gerhard; et al.
Abstract : Background: Fibrosis as a common problem in patients with Crohn's disease is a result of an imbalance toward excessive tissue repair. At present, there is no specific treatment option. Pirfenidone is approved for the treatment of idiopathic pulmonary fibrosis with both antifibrotic and anti-inflammatory effects. We subsequently investigated the impact of pirfenidone treatment on development of fibrosis in a new mouse model of intestinal fibrosis. Methods: Small bowel resections from donor mice were transplanted subcutaneously into the neck of recipients. Animals received either pirfenidone (100 mg/kg, three times daily, orally) or vehicle. Results: After administration of pirfenidone, a significantly decreased collagen layer thickness was revealed as compared to vehicle (9.7 ± 1.0 versus 13.5 ± 1.5 µm, respectively, ** P < 0.001). Transforming growth factor–β and matrix metalloproteinase–9 were significantly decreased after treatment with pirfenidone as confirmed by real-time PCR (0.42 ± 0.13 versus 1.00 ± 0.21 and 0.46 ± 0.24 versus 1.00 ± 0.62 mRNA expression level relative to GAPDH, respectively, * P < 0.05). Significantly decreased transforming growth factor–β after administration of pirfenidone was confirmed by Western blotting. Conclusion: In our mouse model, intestinal fibrosis can be reliably induced and is developed within 7 days. Pirfenidone partially prevented the development of fibrosis, making it a potential treatment option against Crohn's disease–associated fibrosis.